Continued formation of teachers: building possibilities for the teaching of athletics in school Physical Education - Faganello Gemente, Florence Rosana; Matthiesen, Sara Quenzer [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2017)
This research aimed to offer a course of continued formation of teachers, directed to the development of athletics in physical education in school, while checking its contributions to the pedagogical practice of the participants. For the development of the research, we carried out a course of continued formation for teachers, with the participation of 21 teachers of physical education of municipal schools of the state of Goiania. With a qualitative nature, and action research elements, this research used different techniques to survey data, those being: interviews, questionnaires, recordings and field diaries. The results revealed that the course of continued formation provided an opportunity for teachers to exchange experiences; it also provided construction of knowledge that helped to overcome the difficulties in dealing with the athletic modalities approached in the course; it met the needs of the teachers; provided direct interference in school during the process of continued formation; stimulated creativity for the development of new practices; provided raising of the self-esteem of teachers and brought school and university together. Based on the results, we reinforce the importance of continued formation for the construction of new knowledge. We also emphasize the importance of bringing university and school together, in order to enable reflection, discussion, construction and dissemination of new knowledge related to athletics, so that teachers can overcome difficulties to develop pedagogical methods that address these practices in a deeper and more complete way.
Keywords: Athletics; Physical Education in school; Continued formation